Costing Report for CGIAR-NARES-SME - East Africa Maize Breeding Network Operations - Das, Aparna; Teklewold, Adefris; Awalla, Boniface; Kwemoi, Daniel; Kyando, Aggrey; Biratu, Wakuma; Musundire, Lennin; Das, Biswanath (2024)
The report presents the findings from the costing analysis done for the East Africa maize breeding networks. It includes information about network members, market segments and associated areas, partner roles, estimated costs, and the network's Trait Product Profiles (TPP).